Fast‐Charge Limitations for Graphite Anodes with Si as Capacity‐Enhancing Additive. Issue 1 (10th September 2020) - Jeschull, Fabian; Trabesinger, Sigita
Abstract: Rate capability is always coming into the question when new materials are characterized; however, this question also arises when blends of different electroactive materials are used. This study was dedicated to the charge capabilities of graphite‐Si blends, in which Si acts as a capacity‐enhancing electrode additive (≤20 wt.% Si). As delithiated Si is considered poorly electronic conductor, one would assume that the presence of Si induces additional internal resistance that hampers fast charging of this type of electrodes. Current‐interruption measurements demonstrate that the internal resistance of graphite‐Si blends increases proportionally to the amount of Si in the electrode. This is also reflected in the respective charge capability tests, where electrodes with smaller Si content showed better power performance. With the aim to improve the charge capability of the electrode formulations, two approaches were evaluated: 1) addition of various amounts of conductive additive in the form of carbon black and 2) densification of electrodes. While the charge capability could be successfully improved by increasing carbon black content, densification mainly lead to performance deterioration. Abstract : Are Si nanoparticles limiting fast‐charging in graphite‐Si blends ? The charge capabilities of graphite electrodes containing different amounts of Si nanoparticles as capacity enhancing additive are investigated. Tracking the cell resistance, in dependence of Si content, suggests a bottleneck in the early stages of lithiation, when the alloying reaction is the primary process. Two common strategies are examined to improve the charge capability of these electrode blends.